The Effect of Peer Group Education on Nurses’ Ability to Implement an Early Warning System for Stroke Patients - Siswanto Agung Wijaya; Eni Sumarliyah; Fathiya Luthfil Yumni; Wiwin Risnawati; Melli Mufidah (Adi Husada Nursing Journal, 2026)
Nurses face challenges with Early Warning System (EWS) assessments, which can delay the identification of deteriorating conditions in stroke patients, increasing the risk of severe outcomes like unplanned ICU transfers, cardiac arrest, and mortality. This study aimed to determine the effect of peer group education on nurses’ ability to perform the Early Warning System in stroke patients. This study used pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 30 nurses selected using purposive sampling at the Multazam Stroke Unit of Haji General Hospital, East Java, Surabaya. Data were collected using an observation checklist to assess nurses’ ability in implementing the EWS before and after a peer group education intervention. The intervention was conducted in two 60-minute sessions delivered by the researcher and included education on the concept of EWS, EWS procedures for stroke patients, and practical training on EWS implementation through lectures, discussions, question-and-answer sessions, and evaluation activities. Data were analyzed using the Wilcoxon Signed Rank Test. Prior to the intervention, 56.7% of nurses had adequate ability and 43.3% had good ability in implementing the EWS. Following the peer group education intervention, all nurses (100%) demonstrated good ability. Statistical test showed a significant improvement in nurses’ ability following the intervention (p = 0.000). Peer group education was effective in improving nurses’ ability to implement the EWS for stroke patients. This educational approach may be used as a continuing professional development strategy to enhance nurses’ competence in early detection and management of patient deterioration in clinical settings.